Recent experiences with surges in capital inflows - Schadler, Susan... [et al] (IMF WashingtonUS, 1993)
Reviews the experiences of six countries that have had recent surges in capital inflows viz. Chile, Colombia, Egypt, Mexico, Spain and Thailand.